Comprehensive insights into cytomegalovirus anterior segment infections: A narrative review - Yih-Shiou Hwang; Po-Yi Wu; Eugene Yu-Chuan Kang; Wei-Chi Wu; Linda Yi-Hsing Chen; Chi-Chun Lai; Kyung Seek Choi (Taiwan Journal of Ophthalmology, 2025)
Cytomegalovirus (CMV) anterior uveitis (AU), a significant cause of intraocular inflammation, is increasingly recognized in immunocompetent individuals, often leading to visual morbidity if not promptly addressed. The diagnosis of CMV AU is challenging, owing to its variable clinical manifestations, which can overlap with other forms of AU. CMV AU should be suspected in corticosteroid-recalcitrant inflammatory ocular hypertensive syndrome or corneal endotheliitis with coin-shaped keratic precipitates (KPs). CMV AU differs from herpes simplex virus and varicella-zoster virus AU with milder symptoms, less ciliary injection, smaller KPs, higher intraocular pressure (IOP), and diffuse iris atrophy. Aqueous humor analysis, specifically polymerase chain reaction (PCR), is the gold standard for diagnosis, detecting viral DNA, and quantifying disease severity. While highly effective, PCR can yield false negatives with low viral loads. Clinical judgment remains crucial, alongside PCR results. Early diagnosis and targeted antiviral treatment are key to preserving visual function and preventing complications, such as glaucoma and keratopathy. CMV AU treatment aims to control inflammation, reduce viral activity, and prevent complications. Antiviral therapy is crucial, with topical ganciclovir (GCV) gel often first line. Oral valganciclovir is used for systemic treatment, especially in severe cases. Intravitreal GCV may be used in severe cases, often followed by systemic therapy, but its role remains suspicious. Corticosteroids should only be used with antiviral therapy. Topical corticosteroids manage inflammation and are tapered over time. IOP management is also essential, potentially requiring surgery. Treatment duration varies, and long-term maintenance may be necessary. More research is needed to standardize treatment protocols and further understand the pathogenesis and immunopathogenesis of CMV anterior uveitis.